Graduate unemployment problem in Bangladesh: causes and the way forward - Arab, Arab Ali (Journal of Management and Business Education, 2025)
The unemployment problem accelerates the vicious severe circle of poverty that signifies the migration of young and unmarried people to urban areas. The unemployment rate, particularly, the graduate unemployment rate has significantly increased in recent years in Bangladesh. Noticeably, tertiary-level education produces millions of graduates from different academic fields who are sternly suffering from job crises that cause a high rate of graduate unemployment problem in Bangladesh. The Labour Force Survey (LFS)-2024 of The Bangladesh Bureau of Statistics (BBS) showed the unemployment at 3.65%, on the other hand, the unemployment rate among tertiary-educated youth increased to 27.8% cent in 2022 from 9.7 % in 2013 (World Bank-2024). Inevitably, to achieve Sustainable Development Goals (SDGs)-2030 and augment holistic development in Bangladesh, incorporating those youth into the country's workforce is a crucial need. From the above perspective, the question is “why do graduate of Bangladesh remain unemployed and their number is increasing day by day?” At the same time what possible initiatives can be taken to ensure employment for the graduate after their graduation? Through the critical study of contemporary literature, journals, professional magazines, and national and international print and online newspapers, the author aims to find out the main causes of graduate unemployment in Bangladesh and the possible initiatives to reduce this problem from the experiences of other countries. The author found some significant causes that impede the graduates getting job and showed some outstanding initiatives and approaches experienced from Japan, Malaysia, India, and Sri Lanka for sustainably ensuring graduate employment in Bangladesh. However, it suggests further empirical research on the correlation among the causes of the graduate unemployment problem in Bangladesh. Consequently, having graduated in different academic fields, graduates of Bangladesh are severely suffering from job crises that are increasing daily. The author found that low STEM (Science, Technology, Engineering, and Mathematics) graduates, demographic dividends against severe job crises, and structural mismatches between graduates and job market demand are the root causes of graduate unemployment in Bangladesh. This study suggests introducing a competency-based, job-oriented combined curriculum and technical education for quickly entering the job market.